Religious values in the formation of human capital in Russia - Zinkovskii, Sergey; Schastlivaya, Tatyana; Maslov, Dmitry (Opción, 2019)
The article discusses the role of religious values in the formation of human capital -the main indicators of which are the level of education, life expectancy, as well as the average level of wages - on the example of various regions of the Russian Federation via the average multidimensional method. As a result, the state provides access to education for everyone, which implies an increase in the value of human capital. In conclusion, no significant differences were found in health, education or culture indicators for the population dominated by Christianity, Islam or Buddhism.